THE INFLUENCE OF COMPETENCE, MOTIVATION AND INCENTIVES ON THE PERFORMANCE OF QURAN TEACHERS IN IZZUDIN INTEGRATED ISLAMIC SCHOOLS - Tien Yustini; Marzuki Alie; Ali Amrullah (Jurnal Ekonomi, 2023)
This study aims to analyze and prove the effect of competence, motivation, and incentives on the performance of Qur'an teachers at the Izzuddin Integrated Islamic School, both partially and simultaneously. This research is a quantitative study using descriptive methods and using multiple linear analysis techniques to analyze the data. The population of this research is 100 employees of SIT Izzuddin Palembang. The sampling technique used was the purposive sampling technique, namely the total sampling method because all members of the population were used as samples. The data analysis technique used is the instrument test (validity test and reliability test), regression test (multiple linear regression, correlation coefficient, and determination), and hypothesis testing (F test and t-test). As well as passing the normality test and being free from multicollinearity and heteroscedasticity tests. The results showed that the t value of the competency variable (3,303) > t table (990,102) means that there is an influence between competence on teacher performance, the t value of motivation variable (3,227) > t table (990,102) means that there is an influence between motivation on teacher performance, and the calculated t value of the incentive variable (3,341) > t table (990,102) means that there is an effect of incentives on teacher performance. The calculated F value of competency, motivation, and incentive variables is (49,840) and it is known that the coefficient value is sig. Fcount of 0.000 <P-value (α) of 0.05 (0.000 <0.05). Based on the test criteria, if the coefficient is sig. Fcount < P-value (α) of 0.05 (0.000 <0.05), meaning that Ha is accepted and Ho is rejected, it can be concluded that there is a significant relationship between Competence (X1), Motivation (X2), Incentives (X3), on Teacher Performance (Y), and this research also shows that competency, motivation and incentive variables partially and together have a positive and significant influence on teacher performance. The managerial implications of this research are expected to be input for SIT IZZUDDIN, that competency, motivation, and incentive factors are also factors that affect performance, especially the performance of Al-Qur'an teachers. And it is hoped that the management of these factors can be optimized in order to improve performance.